Effectiveness of two different behavioral modification techniques among 5-7-year-old children: A randomized controlled trial - Aruna Prashanth Vishwakarma; Prashant Arjun Bondarde; Sudha Bhimangouda Patil; Arun Suresh Dodamani; Prashanth Yachrappa Vishwakarma; Shoeb A Mujawar (Wolters Kluwer Medknow Publications, 2017)
Background: Dental fear is a common, essential, and inevitable emotion that appears as a response to the stressful situation, which raises children's anxiety level, resulting in reduced demand for pediatric dental care. Aims: (1) To compare and evaluate the effectiveness of customized tell-play-do (TPD) technique with live modeling for behavior management of children. (2) To compare the behavioral modification techniques in managing the children during their dental visits. Materials and Methods: Ninety-eight children aged 5-7 years were enrolled in the study and randomly allocated into two groups. Phase I: first visit. Group I - children were conditioned to receive various dental procedures using live modeling followed by oral prophylaxis. Group II - TPD technique was introduced with customized playing dental objects followed by oral prophylaxis. Phase II: second visit. After 7 days interval, all the study subjects were subjected to rotary restorative treatment. Evaluation: Heart rate, Facial Image Scale (FIS), and Venham-6-point index were used before intervention, after intervention, and during dental procedure to quantify the anxious behavior. Results: All 98 children after intervention underwent oral prophylaxis on first visit and rotary restorative treatment on second visit. The average pulse rate, FIS, and Venham scale scores were significantly lower among children who received TPD intervention when compared to those who received live modeling intervention. Unpaired t-test at 5% level of significance was considered as statistical significance. Conclusions: TPD is effective in reducing children's fear and anxiety about dental treatment, children enjoy playing with customized dental object. Thus, to promote adaptive behavior, TPD could be an alternate behavioral modification technique during pediatric dentistry.